Correction: The Methanol Poisoning Outbreaks in Libya 2013 and Kenya 2014. - Morten Rostrup; Jeffrey K Edwards; Mohamed Abukalish; Masoud Ezzabi; David Some; Helga Ritter; Tom Menge; Ahmed Abdelrahman; Rebecca Rootwelt; Bart Janssens; Kyrre Lind; Raido Paasma; et al. (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0152676.].